Identification Of Selected Polyphenols In The Leaves Of Purple Coneflower (Echinacea Purpurea) - I.R. Asqarov; M.M. Mo‘minjonov; M.M. Mo‘minjonov (Academia One Publishing, 2025)
This study presents the results of the identification of selected polyphenolic compounds in the leaves of Echinacea purpurea (purple coneflower) cultivated in Uzbekistan, using highperformance liquid chromatography (HPLC). The analysis focused on quantifying key bioactive compounds such as rutin, salicylic acid, quercetin, and apigenin, which are known for their therapeutic and antioxidant properties. The findings contribute to the phytochemical characterization of Echinacea purpurea and highlight its potential as a natural source of healthpromoting substances in the development of functional foods and herbal medicines.
Keywords: Echinacea purpurea; leaf; polyphenol